Comparison of film measurements and Monte Carlo simulations of dose delivered with very high‐energy electron beams in a polystyrene phantom. Issue 4 (17th March 2015) - Bazalova‐Carter, Magdalena; Liu, Michael; Palma, Bianey; Dunning, Michael; McCormick, Doug; Hemsing, Erik; Nelson, Janice; Jobe, Keith; Colby, Eric; Koong, Albert C.; Tantawi, Sami; Dolgashev, Valery; et al.
Abstract : Purpose: To measure radiation dose in a water‐equivalent medium from very high‐energy electron (VHEE) beams and make comparisons to Monte Carlo (MC) simulation results. Methods: Dose in a polystyrene phantom delivered by an experimental VHEE beam line was measured with Gafchromic films for three 50 MeV and two 70 MeV Gaussian beams of 4.0–6.9 mm FWHM and compared to corresponding MC‐simulated dose distributions. MC dose in the polystyrene phantom was calculated with the EGSnrc/BEAMnrc and DOSXYZnrc codes based on the experimental setup. Additionally, the effect of 2% beam energy measurement uncertainty and possible non‐zero beam angular spread on MC dose distributions was evaluated. Results: MC simulated percentage depth dose (PDD) curves agreed with measurements within 4% for all beam sizes at both 50 and 70 MeV VHEE beams. Central axis PDD at 8 cm depth ranged from 14% to 19% for the 5.4–6.9 mm 50 MeV beams and it ranged from 14% to 18% for the 4.0–4.5 mm 70 MeV beams. MC simulated relative beam profiles of regularly shaped Gaussian beams evaluated at depths of 0.64 to 7.46 cm agreed with measurements to within 5%. A 2% beam energy uncertainty and 0.286° beam angular spread corresponded to a maximum 3.0% and 3.8% difference in depth dose curves of the 50 and 70 MeV electron beams, respectively. Absolute dose differences between MC simulations and film measurements of regularly shaped Gaussian beams were between 10% and 42%. Conclusions: The authors demonstrate that relative dose distributions for VHEE beams of 50–70 MeV can be measured with Gafchromic films and modeled with Monte Carlo simulations to an accuracy of 5%. The reported absolute dose differences likely caused by imperfect beam steering and subsequent charge loss revealed the importance of accurate VHEE beam control and diagnostics.